Access to Information for Small Business Managers: Examination of Some Strategies and Values - Bouthillier, France (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Understanding how specific groups of users access information is central for developing adequate library and information services and systems. The paper presents preliminary and partial results of a study on the information needs of small business managers and their information service requirements. The study aimed at identifying a service model that would fit the needs and requirements. . .